Analysis of electromagnetic field polarizations in multiantenna systems. - Svantesson, T.
This paper provides an analytical framework useful for assessing the use of all six electric and magnetic electromagnetic field polarizations for multiantenna communications systems. The approach uses a mapping between the induced signal currents and the received electromagnetic field in order to formulate a diversity interpretation of the six-polarization problem. Application of the framework to a simple, yet representative, channel model demonstrates that for full multipath elevation and azimuthal angle spread, six communication modes are theoretically possible. However, to implement the system requires more antenna design work since a straightforward implementation is found to reduce the potential number of modes to three.
Keywords: Antenna radiation patterns; Array antenna; Channel capacity; Correlation method; Diversity reception; Electric electromagnetic field polarization; Induced signal currents; Magnetic electromagnetic field polarization; Multiantenna communication system; Multiple input multiple output channel